Implementation of the Campus Teaching Program Batch 3 in Building Scientific Literacy in Elementary Schools - Jamilah; Yeni Puji Astuti; Muhammad Misbahudholam AR (Postgraduate, University of Mataram, 2023)
Scientific literacy is using scientific knowledge to identify questions, acquire new knowledge, explain scientific phenomena, and draw conclusions based on scientific evidence. Implementation of the Campus Teaching Program Batch 3 is the realization of the independent learning curriculum core program movement, which aims to empower human resources, especially students. This study uses a qualitative descriptive research method. The research was conducted at Lenteng Barat IV Elementary School in Lenteng Barat Village, Lenteng District, Sumenep Regency, East Java, as the target school for the 3rd batch of campus teaching programs. Data collection techniques in this study used structured interviews; the researchers interviewed school principals, class teachers, and students who passed the Campus Teaching Program Batch 3. According to the interviews conducted with the respondents, the survey results said that implementing the Campus Teaching Program Batch 3 in building scientific literacy was very high/good. Seeing the study results, the researchers suggested developing scientific literacy and numeracy instruments in elementary schools.